Indicators of ADP-induced platelet aggregation in patients with hypertension complicated by ischemic hemisphere stroke - Syvolap, V. V.; Zhemanyuk, S. P. (Zaporozhye Medical Journal, 2017)
Arterial hypertension is one of the most significant factor in the development of cardio-vascular complications in patients due to elevated blood pressure, maintenance of disorders of endothelial function and coagulation system, as well as changes in platelets function. The purpose of the work was to determine the characteristics of ADP-induced platelet aggregation in hypertension patients with ischemic hemisphere stroke. Material and methods. The enrolled patients (n =152) were divided into 3 groups. The first one included 38 patients (an average age of 64 [57−72] years, (male 35%)) with arterial hypertension (AH) who reached the target level of blood pressure (according to the «office» measurements and ambulatory blood pressure monitoring). The second group included 96 AH patients aged 60 [64−71] years, (62% men) who did not reach the target level of blood pressure. And the third group involved 18 patients aged 66 [66−72] years (male 56%) with AH complicated by ischemic hemisphere stroke. Platelet aggregation was performed using light transmittance aggregation by optical analyzer (Solar, R.B.) with adenosine 5’-diphosphate (Sigma-Aldrich) at final concentration of 10.0 × 106 mol / L. Results. There were significantly higher rates in hypertensive patients with ischemic hemisphere stroke of the maximum degree of platelet aggregation in 10 minutes (Tmax, 10min) by 18 % (78 [78−100] % vs. 66 [57−83] %, respectively, U = 554.0; p = 0.015), the maximum aggregation time (tTmax, 10min) by 34 % (78 [78−100] s vs. 66 [57−83] s, respectively, U = 554.0, p = 0.015). The degree of platelet aggregation at the end of the recording time (T 10min) and the area under the curve of the end of the 10 min. (AUC10min), respectively, by 19.4 % and 15 % than in AH patients who have not reached the target level of blood pressure. Conclusions. Hypertensive patients who did and did not reach the target level of blood pressure showed no significant difference in analyzed parameters of ADP-induced platelet aggregation. However, there was approximately twofold increase in deaggregation (Kdesagg, 10min) among patients who did not reach the target level of blood pressure compared with those who reached it. Meanwhile, hypertensive individuals with ischemic hemisphere stroke had significantly higher ADP−induced aggregation parametrs as percentage of aggregation during 10 min. (T10min), the area under the aggregation curve at the end of 5th (AUC5min) and 10th min. (AUC10min) in comparison to hypertensives who did not reach the target blood pressure level. The influence of drugs on the studied parameters of ADP-induced platelet aggregation in patients is not established.